Serological evidence of exposure to toxoplasma gondii and neospora caninum in free-ranging Orinoco goose (Neochen Jubata) in Brazil - André, Marcos Rogério [UNESP]; De Santi, Mariele [UNESP]; Luzzi, Mayara De Cássia [UNESP]; De Oliveira, Juliana Paula [UNESP]; Fernandes, Simone De Jesus [UNESP]; Machado, Rosangela Zacarias [UNESP]; Werther, Karin [UNESP] (FapUNIFESP (SciELO), 2019)
Toxoplasma gondii and Neospora caninum are Apicomplexan intracellular protozoan parasites that affect numerous animal species, thus leading to severe diseases and economic losses, depending on the vertebrate species involved. The role of the avian species in maintaining and transmission of these coccidia has been studied for several years as they tend to serve as a potential source of infection for mammals and humans. The present study aimed to assess the serological exposure of Orinoco goose (Neochen jubata) to T. gondii and N. caninum. Between 2010 and 2013, 41 free-ranging Orinoco geese were captured in the Araguaia River, Brazil. The presence and titration of IgY antibodies to both coccidia were assayed via indirect immunofluorescent antibody test (IFAT). While IgY antibodies for N. caninum were present in 5 animals, with titers of 20, the antibodies for T. gondii were found in 35 animals, with titers ranging from 20 to 640. Considering that the Orinoco goose’s meat is consumed by the local population in the studied area, it may represent an important source of T. gondii infection for humans. Due to its migratory behavior, this goose may play a pivotal role in the natural dispersion of both parasites. Furthermore, molecular studies are required for genotyping the isolates of T. gondii that occurs in this avian species.
Evidência sorológica de exposição à Toxoplasma gondii e Neospora caninum em Ganso-do-Orinoco (Neochen Jubata) de vida livre no Brasil
Keywords: Neosporosis; Orinoco goose; Serology; Toxoplasmosis